An Unusual Renal Mass in Adolescent - Case Report and Literature Review (2019)
Introduction Renal neoplasms in pediatrics and adolescents patients are rare entities, 6-7% masses in pediatrics. In teenagers, set a noteworthy clinical challenge. Can manifest as variable signs or be asymptomatic. In scientific papers, Renal Cell Carcinoma and Wilms' tumor have been identified as the most prevalent tumors in aged lesser than 20 years; Metanephric Adenoma is an unusual pathologic entity into this population. Case Report A female youngster case, with left flank pain and monosymptomatic macroscopic hematuria, imaging studies show up a neoplastic appearance lesion at left kidney, demonstrated as Metanephric Adenoma afterwards by immunohistochemistry analysis. Literature review is performed by searching in the last three decades. Patient was taken to left radical nephrectomy, later the pathological analysis suggests Metanephric Adenoma, and with immunohistochemistry markers is supported this finding. Conclusions Renal masses in adolescents are uncommon. It is needed high clinical suspicion, a thorough physical examination and imaging techniques aid. Conventionally, histopathology determine diagnosis, although in some cases when doubt last, it is necessary perform immunohistochemistry. Renal Cell Carcinoma is the most prevalent in youth's renal masses, but there are indistinguishable conditions on imaging that raise a defiant clinical scenario; it is the purpose to provide a clinical guidance tool in the approach of Metanephric adenoma and contribute to the development of knowledge in a scarcely documented clinicopathological entity that doubtlessly will reverberate in best clinical practice and echo at science, social and economics. © 2019 Sociedad Colombiana de Urología.